2021
DOI: 10.1101/2021.06.07.21258457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome and epigenome wide studies of plasma protein biomarkers for Alzheimer’s disease implicate TBCA and TREM2 in disease risk

Abstract: The levels of many blood proteins are associated with Alzheimer′s disease or its pathological hallmarks. Elucidating the molecular factors that control circulating levels of these proteins may help to identify proteins causally associated with the disease. Here, genome-wide and epigenome-wide studies (nindividuals≤1,064) were performed on plasma levels of 281 Alzheimer′s disease-associated proteins, identified by a systematic review of the literature. We quantified the contributions of genetic and epigenetic v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 90 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…3). When accounting for 26 pQTMs that were previously reported by Zaghlool et al and 10 pQTMs that were previously reported by Hillary et al 14,19 , 2892 of the 2928 fully-adjusted pQTMs were previously unreported. Of these 2892 pQTMs, 1109 involved the levels of 41 proteins that were measured by Zaghlool et al (973 pQTMs for PAPPA and 136 additional pQTMs for the levels of 40 proteins), whereas 1783 pQTMs involved the levels of proteins that were previously unmeasured (1116 pQTMs for PRG3 and 667 further pQTMs for 148 proteins).…”
Section: Pleiotropic Pqtm Associations In the Fully-adjusted Mwasmentioning
confidence: 82%
See 1 more Smart Citation
“…3). When accounting for 26 pQTMs that were previously reported by Zaghlool et al and 10 pQTMs that were previously reported by Hillary et al 14,19 , 2892 of the 2928 fully-adjusted pQTMs were previously unreported. Of these 2892 pQTMs, 1109 involved the levels of 41 proteins that were measured by Zaghlool et al (973 pQTMs for PAPPA and 136 additional pQTMs for the levels of 40 proteins), whereas 1783 pQTMs involved the levels of proteins that were previously unmeasured (1116 pQTMs for PRG3 and 667 further pQTMs for 148 proteins).…”
Section: Pleiotropic Pqtm Associations In the Fully-adjusted Mwasmentioning
confidence: 82%
“…This suggested that DNAm not only reflects variability in the proteome but is closely related to chronic systemic inflammation. Hillary et al have also assessed epigenetic signatures for 281 SOMAmer protein measurements that were previously associated with Alzheimer’s disease, in the Generation Scotland cohort that we utilised in this study 19 . However, proteome-wide assessment of pQTMs has not been tested against a comprehensive spectrum of brain health traits.…”
Section: Introductionmentioning
confidence: 99%
“…3). When accounting for 26 pQTMs that were previously reported by Zaghlool et al and 10 pQTMs that were previously reported by Hillary et al 14,19 , 2,892 of the 2,928 fully-adjusted pQTMs were novel. Of these 2,892 novel pQTMs, 1,109 involved the levels of 41 proteins that were measured by Zaghlool et al (973 pQTMs for PAPPA and 136 additional pQTMs for the levels of 40 proteins), whereas 1,783 pQTMs involved the levels of proteins that were previously unmeasured (1,116 pQTMs for PRG3 and 667 further pQTMs for 148 proteins).…”
Section: Pleiotropic Pqtm Associations In the Fully-adjusted Mwasmentioning
confidence: 83%
“…Three associations did not replicate at nominal P < 0.05; however, the direction of effect was consistent in all cases. There were 2,854 novel SOMAmer pQTM associations in the protein EWAS, when accounting for 41 associations that were previously reported by EWAS from Zaghlool et al (31 associations) and Hillary et al (10 associations) 1,18 . In addition to the 1,141 pQTMs involving PAPPA, there were 1,157 pQTMs that involved the Proteoglycan 3 Precursor (PGR3) protein.…”
Section: Epigenome-wide Studies Of 4235 Plasma Proteinsmentioning
confidence: 84%
“…An additional level of information that can inform causal relationships between genotype and phenotype is the proteome [98], which in addition to interpretation of GWA and TWA results, can provide targets for future functional studies and drug targets [99]. Proteome-wide association studies aggregate the signal of all variants that jointly affect a protein-coding gene and assess their overall impact on the protein's function and the phenotype of interest [100].…”
Section: Combining Multi-omics Data For Prediction and Fine-mapping U...mentioning
confidence: 99%